Utilization of Coffee Skin Waste as Compost Fertilizer in Tapak Gedung Village, Kepahiang - Maryanti, Evi; Rahma, Zahra Kamila; Lesmi, Jenny Atri; Agus, Mita Putri; Yanty, Mona Kristi; Habibah, Putri Evony (Asosiasi Profesi Multimedia Indonesia, 2023)
Tapak Gedung is a village where most residents work as coffee farmers. This means that this village has a lot of coffee skin waste. This coffee skin waste is just left to lie around without being processed into something useful. Therefore, Thematic KKN students developed compost fertilizer from coffee skin waste in Tapak Gedung village which aims to optimize the natural potential in the form of abundant but unutilized coffee skins. This product has utility value for village communities, especially farmers, the majority of whom live in the village. Using coffee skin waste as a basic material in the composting process is an efficient solution to reduce the amount of coffee skin waste in the village. The decomposition process is accelerated by the addition of EM4 bacteria, helping in the decomposition of manure thereby optimizing the composting process. Compost is made from 80 kg of coffee husk bran, 200 mL of EM4 diluted with 18 L of water, 20 kg of animal waste, and 1 kg of urea. Thematic KKN students conveyed information about composting coffee husk waste to the Tapak Gedung village community through outreach, discussions and PowerPoint slide presentations. As a result, the compost that has been produced is distributed to village communities and applied to crops and agricultural land.